Law, finance, economic growth and welfare: why does legal origin matter? - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2011)
This paper proposes and empirically validates four theories of why legal origin influences growth and welfare through finance. It is a natural extension of Law and finance: why does legal origin matter? by Thorsten Beck, Asli Demirgüç-Kunt and Ross Levine (2003). We find only partial support for the Mundell (1972), La Porta et al. (1998) and Beck et al. (2003) hypotheses that English common-law countries tend to have better developed financial intermediaries than French civil-law countries. While countries with English legal tradition have legal systems that improve financial depth, activity and size, countries with French legal origin overwhelmingly dominate in financial intermediary allocation efficiency. Countries with Portuguese legal origin fall in-between.
Keywords: G2; K2; K4; O1; P5; 330; Law; Financial development; Growth; Welfare